High-toughness martensitic steel and preparation process thereof
By introducing yttrium elements into martensitic steel, modifying impurities and purifying the liquid steel, the problems of poor steel toughness and unused impurities are solved, and martensitic steel with high toughness and good processing performance are achieved.
Patent Information
- Application Number
- CN202411519580.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the toughness of steel materials is poor and impurities are not fully utilized, resulting in insufficient performance.
By introducing yttrium elements into martensitic steel, rare earth oxides or rare earth sulfides are formed, impurities are modified and liquid steel is purified, thereby improving the toughness of the steel.
It effectively improves the toughness of martensite steel, and avoids the formation of low-melting eutectic phases between yttrium and copper during smelting caused by excessive yttrium content, reducing the difficulty of forging.
Smart Images

Figure CN119571209A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting, and in particular to a high-toughness martensitic steel and a preparation process thereof. Background Art
[0002] Copper-containing high-strength steel is a martensitic steel that relies on the strengthening of second-phase copper particles. Through quenching treatment, it forms fine and evenly distributed martensitic grains, which can significantly improve the performance of martensitic steel. Because of its ultra-high strength and good welding performance, it is widely used in engineering fields such as shipbuilding and bridge construction. Existing research mainly modifies martensitic steel by adding alloy or non-metallic elements to optimize its strength, heat resistance, wear resistance and other properties, but the addition of each element will inevitably cause the introduction of impurities, such as the introduction of aluminum oxide or manganese sulfide, which reduces the toughness of martensitic steel and also affects the processing performance.
[0003] The prior art discloses a manufacturing process for a high-strength rolling roller and a heat treatment device used in the manufacturing process. The high-carbon steel is preheated and immersed in deionized water to remove impurities inside the high-carbon steel, thereby ensuring the quality of the final product and increasing the service life. However, the problem of poor toughness of the steel is not solved. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor toughness of steel in the prior art, thereby providing a high-toughness martensitic steel and a preparation process thereof.
[0005] Another technical problem to be solved by the present invention is to overcome the defect that impurities in steel materials in the prior art are not fully utilized, thereby providing a high-toughness martensitic steel and a preparation process thereof.
[0006] To this end, the present invention provides a high-toughness martensitic steel, comprising the following components in mass fractions:
[0007] C: 0.023% ~ 0.05%, Cu: 1.5% ~ 2%, Ni: 8.59% ~ 9%, Mn: 0.55% ~ 0.6%, Cr: 0.85% ~ 0.9%, Mo: 0.85% ~ 0.9%, V: 0.2% ~ 0.25%, Y: 0.013% ~ 0.047%, and the rest are Fe and unavoidable impurities.
[0008] In some of the embodiments, under the field of view of a scanning electron microscope at 1000X, the matrix of the high-toughness martensitic steel contains rare earth compounds, and the number of the rare earth compounds is 5-10.
[0009] In some embodiments, the rare earth compound includes at least one of a rare earth oxide or a rare earth sulfide.
[0010] Preferably, the particle size of the rare earth compound is 1-5 μm.
[0011] In some embodiments, the present invention provides a process for preparing high-toughness martensitic steel, comprising the following steps:
[0012] Martensitic steel is obtained by vacuum melting, forging and quenching various metal materials and carbon in a certain proportion.
[0013] Preferably, during vacuum melting, yttrium is laid on the bottom of the ingot mold, and the particle size of the yttrium is 100-200 mesh.
[0014] In some embodiments, the metal material includes copper, nickel, manganese, chromium, molybdenum, vanadium and yttrium.
[0015] In some of the embodiments, the mass fractions of the raw materials for preparing the steel ingot are: carbon powder 0.04%-0.06%, copper block 1.45%-3.24%, nickel block 8.8%-9.5%, manganese block 0.5%-0.7%, chromium block 0.8%-0.95%, molybdenum block 0.8%-0.95%, vanadium block 0.15%-0.3% and yttrium powder 0.05%-0.15%, and the rest are iron blocks.
[0016] In some of the embodiments, the mass fractions of the raw materials for preparing the steel ingot are: 0.05%-0.055% carbon powder, 1.5%-3% copper block, 9%-9.2% nickel block, 0.55%-0.6% manganese block, 0.85%-0.9% chromium block, 0.85%-0.9% molybdenum block, 0.2%-0.25% vanadium block and 0.05%-0.12% yttrium powder, and the rest are iron blocks.
[0017] Preferably, the purity of the above components is greater than or equal to 99wt%.
[0018] In some of the embodiments, the vacuum melting temperature is 1530-1600° C., and the melting time is 0.5-1 h.
[0019] In some of the embodiments, the forging temperature is 1100-1150° C., and the forging holding time is 1-2.5 h.
[0020] Preferably, the quenching step is to air-cool the forged material.
[0021] The technical solution of the present invention has the following advantages:
[0022] The present invention provides a high-toughness martensitic steel, comprising the following mass fraction components, C: 0.023% to 0.05%, Cu: 1.5% to 2%, Ni: 8.59% to 9%, Mn: 0.55% to 0.6%, Cr: 0.85% to 0.9%, Mo: 0.85% to 0.9%, V: 0.2% to 0.25%, Y: 0.013% to 0.047%, and the rest is Fe and inevitable impurities. The present invention introduces yttrium elements, on the one hand, can effectively modify impurities and purify molten steel, on the other hand, the rare earth oxides formed by yttrium and impurities exist in the martensitic steel matrix, which can effectively improve the toughness of martensitic steel. At the same time, the present invention limits the mass fraction of yttrium in martensitic steel to 0.013% to 0.047%, which can effectively purify impurities, and at the same time avoid the formation of a low-melting eutectic phase with copper during the smelting process due to excessive yttrium content, thereby reducing the difficulty of subsequent forging. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 is a physical picture of the martensitic steel obtained in Example 1 of the present invention;
[0025] Figure 2 is a microscopic morphology of the martensitic steel matrix obtained in Example 1 of the present invention, Figure 2 The A in it represents an inclusion in the martensitic steel matrix;
[0026] Figure 3 yes Figure 2 Energy spectrum at A in the middle;
[0027] Figure 4 is a physical picture of the martensitic steel obtained in Example 2 of the present invention;
[0028] Figure 5 is a microscopic morphology of the martensitic steel matrix obtained in Example 2 of the present invention, Figure 5 The B in represents an inclusion in the martensitic steel matrix;
[0029] Figure 6 yes Figure 5 Energy spectrum at point B in the middle;
[0030] Figure 7 is a physical picture of the martensitic steel obtained in Example 3 of the present invention;
[0031] Figure 8 is a microscopic morphology of the martensitic steel matrix obtained in Example 3 of the present invention, Figure 8 The C in represents an inclusion in the martensitic steel matrix;
[0032] Fig. 9 yes Figure 8 Energy spectrum at C in the middle;
[0033] Fig.10 This is a physical picture of the martensitic steel obtained in Comparative Example 1 of the present invention;
[0034] Fig.11 is a microscopic morphology of the martensitic steel matrix prepared in Comparative Example 1 of the present invention;
[0035] Fig.12 This is a physical picture of the martensitic steel obtained in Comparative Example 2 of the present invention;
[0036] Fig.13 is a microscopic morphology of the martensitic steel matrix prepared in Comparative Example 2 of the present invention;
[0037] Fig.14 is another microscopic morphology of the martensitic steel matrix prepared in Comparative Example 2 of the present invention;
[0038] Fig.15 This is a physical picture of the martensitic steel obtained in Comparative Example 3 of the present invention;
[0039] Fig.16 is a microscopic morphology of the martensitic steel matrix obtained in Comparative Example 3 of the present invention, wherein Fig.16 1, 2, and 3 represent inclusion 1, inclusion 2, and inclusion 3 in the martensitic steel matrix, respectively;
[0040] Fig.17 yes Fig.16 Energy spectrum at inclusion 1;
[0041] Fig.18 yes Fig.16 Energy spectrum at inclusion 2;
[0042] Fig.19 yes Fig.16 Energy spectrum of inclusion 3;
[0043] Fig. 20 is a physical picture of the martensitic steel obtained in Comparative Example 4 of the present invention;
[0044] Fig.21 is a microscopic morphology of the martensitic steel matrix obtained in Comparative Example 4 of the present invention, wherein Fig.21 1 and 2 in the figure represent inclusions in the martensitic steel matrix;
[0045] Fig. 22 yes Fig.21 Energy spectrum at inclusion 1;
[0046] Fig.23 yes Fig.21 Energy spectrum at inclusion 2. DETAILED DESCRIPTION
[0047] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0048] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0049] Example 1
[0050] This embodiment provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0051] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V, Y and Fe are melted with C in a vacuum induction furnace according to a certain ratio, wherein Y powder is spread on the bottom of the ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1550°C, the melting time is 45 minutes, and a 170kg steel ingot is obtained.
[0052] Among them, there are 0.09kg of carbon powder, 2.9kg of copper blocks, 15.4kg of nickel blocks, 1.0kg of manganese blocks, 1.49kg of chromium blocks, 1.49kg of molybdenum blocks, 0.41kg of vanadium blocks and 0.1kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0053] (2) The steel ingot was heated to 1120°C and maintained for 2 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0054] The actual picture of the martensitic steel obtained in this embodiment is shown in Figure 1 The mass fractions of the components of the martensitic steel prepared in this embodiment are obtained by inductively coupled plasma (ICP) method:
[0055] C: 0.035%, Cu: 1.6%, Ni: 9%, Mn: 0.56%, Cr: 0.87%, Mo: 0.85%, V: 0.2%, Y: 0.013%, and the rest are Fe and inevitable impurities.
[0056] The microstructure of the martensitic steel prepared in this embodiment is scanned and the energy spectrum of the martensitic steel matrix is obtained, see Figure 2-Figure 3 It can be seen that there are a small amount of rare earth oxide modified inclusions in the martensitic steel matrix prepared in this embodiment. The number of rare earth oxides under the 1000× field of view is 9 ( Figure 2 The circled area is rare earth oxide).
[0057] Example 2
[0058] This embodiment provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0059] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V, Y and Fe are melted with C in a vacuum induction furnace according to a certain ratio, wherein Y powder is spread on the bottom of an ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1530° C., the melting time is 1 hour, and a 170 kg steel ingot is obtained;
[0060] Among them, there are 0.085kg of carbon powder, 3.8kg of copper blocks, 15.4kg of nickel blocks, 1.0kg of manganese blocks, 1.52kg of chromium blocks, 1.53kg of molybdenum blocks, 0.425kg of vanadium blocks and 0.1kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0061] (2) The steel ingot was heated to 1100°C and maintained for 2.5 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0062] The actual picture of the martensitic steel obtained in this embodiment is shown in Figure 4 The mass fraction of each component of the martensitic steel prepared in this embodiment is obtained by ICP method:
[0063] C: 0.023%, Cu: 2%, Ni: 8.59%, Mn: 0.58%, Cr: 0.89%, Mo: 0.9%, V: 0.25%, Y: 0.019%, and the rest are Fe and inevitable impurities.
[0064] The microstructure of the martensitic steel prepared in this embodiment is scanned and the energy spectrum of the martensitic steel matrix is obtained, see Figure 5-Figure 6 It can be seen that there are a small amount of rare earth oxide modified inclusions in the martensitic steel matrix prepared in this embodiment. The number of rare earth oxides under the 1000× field of view is 7 ( Figure 5 The circled area is rare earth oxide).
[0065] Example 3
[0066] This embodiment provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0067] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V, Y and Fe are melted with C in a vacuum induction furnace in a certain proportion, wherein Y powder is spread on the bottom of the ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1600°C, the melting time is 0.5h, and a 170kg steel ingot is obtained.
[0068] Among them, there are 0.0935kg of carbon powder, 2.65kg of copper blocks, 15.4kg of nickel blocks, 0.935kg of manganese blocks, 1.655kg of chromium blocks, 1.455kg of molybdenum blocks, 0.34kg of vanadium blocks and 0.2kg of yttrium powder, and the rest are iron blocks, which weigh 153kg.
[0069] (2) The steel ingot was heated to 1150°C and maintained for 1 hour, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0070] The actual picture of the martensitic steel obtained in this embodiment is shown in Figure 7 The mass fraction of each component of the martensitic steel prepared in this embodiment is obtained by ICP method:
[0071] C: 0.05%, Cu: 1.5%, Ni: 8.59%, Mn: 0.55%, Cr: 0.9%, Mo: 0.85%, V: 0.2%, Y: 0.047%, and the rest are Fe and inevitable impurities.
[0072] The microstructure of the martensitic steel prepared in this embodiment is scanned and the energy spectrum of the martensitic steel matrix is obtained, see Figure 8-Figure 9 It can be seen that there are a small amount of rare earth oxide modified inclusions in the martensitic steel matrix prepared in this embodiment. The number of rare earth oxides under the 1000× field of view is 9 ( Figure 8 The circled area is rare earth oxide).
[0073] Example 4
[0074] This embodiment provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0075] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V, Y and Fe are melted with C in a vacuum induction furnace according to a certain ratio, wherein Y powder is spread on the bottom of the ingot mold, the particle size of the Y powder is 100 mesh, the melting temperature is 1600°C, the melting time is 0.5h, and a 170kg steel ingot is obtained.
[0076] Among them, there are 0.092kg of carbon powder, 5.1kg of copper blocks, 16kg of nickel blocks, 0.95kg of manganese blocks, 1.53kg of chromium blocks, 1.55kg of molybdenum blocks, 0.45kg of vanadium blocks and 0.25kg of yttrium powder, and the rest are iron blocks, totaling 148kg of iron blocks.
[0077] (2) The steel ingot was heated to 1150°C and maintained for 1 hour, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0078] The mass fractions of the components of the martensitic steel prepared in this embodiment are obtained by ICP method:
[0079] C: 0.045%, Cu: 2%, Ni: 8.59%, Mn: 0.55%, Cr: 0.9%, Mo: 0.85%, V: 0.2%, Y: 0.047%, and the rest are Fe and inevitable impurities.
[0080] The martensitic steel matrix prepared in this embodiment has a small amount of rare earth oxide modified inclusions, and the number of rare earth oxides under the field of view of a scanning electron microscope at 1000× is at least 5.
[0081] Example 5
[0082] This embodiment provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0083] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V, Y and Fe are melted with C in a vacuum induction furnace in a certain proportion, wherein Y powder is spread on the bottom of the ingot mold, the particle size of the Y powder is 150 mesh, the melting temperature is 1600°C, the melting time is 0.5h, and a 170kg steel ingot is obtained.
[0084] Among them, there are 0.0935kg of carbon powder, 2.8kg of copper blocks, 15.64kg of nickel blocks, 0.95kg of manganese blocks, 1.53kg of chromium blocks, 1.53kg of molybdenum blocks, 0.39kg of vanadium blocks and 0.18kg of yttrium powder, and the rest are iron blocks, which weigh 148kg.
[0085] (2) The steel ingot was heated to 1150°C and maintained for 1 hour, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0086] The mass fractions of the components of the martensitic steel prepared in this embodiment are obtained by ICP method:
[0087] C: 0.05%, Cu: 1.5%, Ni: 8.59%, Mn: 0.55%, Cr: 0.89%, Mo: 0.85%, V: 0.2%, Y: 0.035%, and the rest are Fe and inevitable impurities.
[0088] The martensitic steel matrix prepared in this example has a small amount of rare earth oxide modified inclusions, and the number of rare earth oxides under the field of view of a scanning electron microscope at 1000× is 10.
[0089] Comparative Example 1
[0090] This comparative example provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0091] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V and Y are melted with C in a vacuum induction furnace in a certain proportion, wherein Y powder is spread on the bottom of the ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1550°C, the melting time is 45 minutes, and a 170kg steel ingot is obtained.
[0092] Among them, there are 0.085kg of carbon powder, 3.0kg of copper blocks, 15.4kg of nickel blocks, 1.0kg of manganese blocks, 1.52kg of chromium blocks, 1.52kg of molybdenum blocks, 0.42kg of vanadium blocks and 0.05kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0093] (2) The steel ingot was heated to 1120°C and maintained for 2 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0094] The actual picture of the martensitic steel obtained in this embodiment is shown in Fig.10 The mass fraction of each component of the martensitic steel prepared in this embodiment is obtained by ICP method:
[0095] C: 0.034%, Cu: 1.65%, Ni: 8.92%, Mn: 0.57%, Cr: 0.88%, Mo: 0.86%, V: 0.21%, Y: 0.0009%, and the rest are Fe and inevitable impurities.
[0096] The microstructure of the martensitic steel obtained in this comparative example was scanned, see Fig.11 The scanning electron microscope energy spectrum results of inclusions 1-4 shown in the microscopic morphology of the martensitic steel matrix prepared in this comparative example are shown in Table 1. Fig.11 As can be seen from Table 1, the martensitic steel matrix prepared in this comparative example contains a large number of large-sized inclusions, such as aluminum oxide and manganese sulfide, and the number of inclusions is about 30 at a 1000× field of view.
[0097] Table 1 Fig.11 Scanning spectrum results of inclusions 1-4
[0098]
[0099] “-” in the table means not scanned.
[0100] Comparative Example 2
[0101] This comparative example provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0102] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V and Y are melted with C in a vacuum induction furnace according to a certain ratio, wherein Y powder is spread on the bottom of an ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1550° C., and the melting time is 45 min to obtain a steel ingot;
[0103] Among them, there are 0.085kg of carbon powder, 2.9kg of copper blocks, 15.4kg of nickel blocks, 1.0kg of manganese blocks, 1.50kg of chromium blocks, 1.51kg of molybdenum blocks, 0.42kg of vanadium blocks and 0.05kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0104] (2) The steel ingot was heated to 1120°C and maintained for 2 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0105] The actual picture of the martensitic steel obtained in this comparative example is shown in Fig.12 The mass fraction of each component of the martensitic steel prepared in this embodiment is obtained by ICP method:
[0106] C: 0.034%, Cu: 1.55%, Ni: 9%, Mn: 0.55%, Cr: 0.86%, Mo: 0.85%, V: 0.2%, Y: 0.0017%, and the rest are Fe and inevitable impurities.
[0107] The microstructure of the martensitic steel obtained in this comparative example was scanned, see Figure 13-14 The scanning electron microscope energy spectrum results of inclusions 1-6 shown in the microscopic morphology of the martensitic steel matrix prepared in this comparative example are shown in Table 2. It can be seen that there are a large number of large-sized inclusions, such as aluminum oxide and manganese sulfide, in the martensitic steel matrix prepared in this comparative example. The number of inclusions is about 30 under the 1000× field of view.
[0108] Table 2 Fig.14 Scanning spectrum results of inclusions 1-6
[0109]
[0110]
[0111] “-” in the table means not scanned.
[0112] Comparative Example 3
[0113] This comparative example provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0114] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V and Y are melted with C in a vacuum induction furnace in a certain proportion, wherein Y powder is spread on the bottom of an ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1550°C, and the melting time is 45 minutes to obtain a steel ingot.
[0115] Among them, there are 0.085kg of carbon powder, 3.0kg of copper block, 15.4kg of nickel block, 1.0kg of manganese block, 1.52kg of chromium block, 1.53kg of molybdenum block, 0.425kg of vanadium block and 0.5kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0116] (2) The steel ingot was heated to 1120°C and maintained for 2 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0117] The actual picture of the martensitic steel obtained in this comparative example is shown in Fig.15 It can be seen that the martensitic steel cracks. The mass fraction of each component of the martensitic steel prepared in this comparative example is obtained by ICP method.
[0118] C: 0.035%, Cu: 1.6%, Ni: 9%, Mn: 0.56%, Cr: 0.87%, Mo: 0.85%, V: 0.2%, Y: 0.21%, and the rest are Fe and inevitable impurities.
[0119] The microstructure of the martensitic steel prepared in this comparative example was scanned and the energy spectrum of different impurity sites in the martensitic steel matrix was obtained, see Figure 16-Figure 19 It can be seen that there are a large amount of Cu-Y low melting point phases in the martensitic steel matrix prepared in this comparative example.
[0120] Comparative Example 4
[0121] This comparative example provides a preparation process of martensitic steel, and the specific steps and parameters are as follows:
[0122] (1) Ultrapure metal raw materials of Cu, Ni, Mn, Cr, Mo, V and Y are melted with C in a vacuum induction furnace in a certain proportion, wherein Y powder is spread on the bottom of an ingot mold, the particle size of the Y powder is 200 mesh, the melting temperature is 1550°C, and the melting time is 45 minutes to obtain a steel ingot.
[0123] Among them, there are 0.085kg of carbon powder, 3.2kg of copper blocks, 15.4kg of nickel blocks, 1.0kg of manganese blocks, 1.52kg of chromium blocks, 1.53kg of molybdenum blocks, 0.425kg of vanadium blocks and 0.9kg of yttrium powder, and the rest are iron blocks, which weigh 150kg.
[0124] (2) The steel ingot was heated to 1120°C and maintained for 2 h, then hot forged into a 35 mm thick forged plate and air cooled to room temperature to obtain martensitic steel.
[0125] The actual picture of the martensitic steel obtained in this comparative example is shown in Fig. 20 It can be seen that the martensitic steel cracks. The mass fraction of each component of the martensitic steel prepared in this embodiment is obtained by ICP method.
[0126] C: 0.030%, Cu: 1.6%, Ni: 9%, Mn: 0.55%, Cr: 0.85%, Mo: 0.85%, V: 0.22%, Y: 0.41%, and the rest are Fe and inevitable impurities.
[0127] The microstructure of the martensitic steel prepared in this comparative example was scanned and the energy spectrum of different impurity sites in the martensitic steel matrix was obtained, see Figure 21-23 It can be seen that there are a large amount of Cu-Y low melting point phases in the martensitic steel matrix prepared in this comparative example.
[0128] Experimental example
[0129] Impact tests were carried out on the martensitic steels obtained in Examples 1-5 and Comparative Examples 1-5 with reference to the national standard GB / T 229-2020. The test results are shown in Table 3.
[0130] The impact test was conducted on a V-notch sample for Charpy impact test along the rolling direction, with a size of 10mm×10mm×55mm. The experimental temperature was -84°C, and the sample was placed in a gas liquid nitrogen tank. When the temperature reached -84°C, the temperature was maintained for 0.5h, and then the sample was taken out and struck within 5s (the equipment for the impact test was a pendulum instrumented impact tester, model NI750C).
[0131] Table 3 Martensitic steel toughness test results
[0132]
[0133]
[0134] “-” in the table means that the value cannot be determined.
[0135] According to Table 3, compared with the martensitic steels prepared in Comparative Examples 1-2, which have more large-sized impurities, the martensitic steel provided by the present invention has stronger toughness; the martensitic steels prepared in Comparative Examples 3-5 have a large number of low-melting-point phases, the steel body cracks, and the forging fails. The martensitic steel provided by the present invention is not easy to crack, is easy to forge, and has good toughness.
[0136] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A high-toughness martensitic steel, characterized in that: The following components are included in the mass fraction: C: 0.023% ~ 0.05%, Cu: 1.5% ~ 2%, Ni: 8.59% ~ 9%, Mn: 0.55% ~ 0.6%, Cr: 0.85% ~ 0.9%, Mo: 0.85% ~ 0.9%, V: 0.2% ~ 0.25%, Y: 0.013% ~ 0.047%, and the rest are Fe and unavoidable impurities.
2. The high-toughness martensitic steel according to claim 1, characterized in that: Under a 1000X field of view of a scanning electron microscope, the matrix of the high-toughness martensitic steel contains rare earth compounds, and the number of the rare earth compounds is 5-10.
3. The high-toughness martensitic steel according to claim 2, characterized in that: The rare earth compound includes at least one of a rare earth oxide or a rare earth sulfide.
4. The high-toughness martensitic steel according to claim 3, characterized in that: The particle size of the rare earth compound is 1-5 μm.
5. A process for preparing high-toughness martensitic steel according to any one of claims 1 to 4, characterized in that: The following steps are included: Martensitic steel is obtained by vacuum melting, forging and quenching various metal materials and carbon in a certain proportion.
6. The process for preparing high-toughness martensitic steel according to claim 5, characterized in that: The metal materials include copper, nickel, manganese, chromium, molybdenum, vanadium and yttrium.
7. The process for preparing high-toughness martensitic steel according to claim 6, characterized in that: During vacuum smelting, yttrium is laid on the bottom of the ingot mold, and the particle size of the yttrium is 100-200 mesh; and / or, The mass fractions of the raw materials of the steel ingot are: carbon 0.04%-0.06%, copper 1.45%-3.24%, nickel 8.8%-9.5%, manganese 0.5%-0.7%, chromium 0.8%-0.95%, molybdenum 0.8%-0.95%, vanadium 0.15%-0.3%, yttrium 0.05-0.15%, and the rest is iron blocks.
8. The process for preparing high-toughness martensitic steel according to claim 7, characterized in that: The vacuum smelting has a smelting temperature of 1530-1600° C. and a smelting time of 0.5-1 h.
9. The process for preparing high-toughness martensitic steel according to claim 8, characterized in that: The forging temperature is 1100-1150° C., and the forging holding time is 1-2.5 hours.
10. The process for preparing high-toughness martensitic steel according to claim 9, characterized in that: The quenching step is to air-cool the forged material.